2014
DOI: 10.1007/s13277-014-2343-9
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of flotillin-2 is associated with renal cell carcinoma progression

Abstract: Flotillin-2 (FLOT2) is a highly conserved protein isolated from caveolae/lipid raft domains that tether growth factor receptors linked to signal transduction pathway. FLOT2 has recently been identified to be involved in tumorigenesis of several cancers such as breast cancer, melanoma, and gastric cancer. However, the role of FLOT2 in renal cell carcinoma (RCC) remains unclear. The expression levels of FLOT2 in RCC patients and renal cancer cell lines were evaluated by quantitative real-time PCR (qRT-PCR) and W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 15 publications
2
21
0
Order By: Relevance
“…43 Flotillins have recently been implicated in the tumorigenesis of several cancers such as breast cancer, gastric cancer and renal cell carcinoma. [44][45][46] This study revealed an important function of flotillin-1 in H-Ras activation and invasion in breast cancer cells. In addition, our results from a xenograft model and clinical studies show that flotillin-1 may play a significant role in the tumorigenicity and aggressiveness of TNBC.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…43 Flotillins have recently been implicated in the tumorigenesis of several cancers such as breast cancer, gastric cancer and renal cell carcinoma. [44][45][46] This study revealed an important function of flotillin-1 in H-Ras activation and invasion in breast cancer cells. In addition, our results from a xenograft model and clinical studies show that flotillin-1 may play a significant role in the tumorigenicity and aggressiveness of TNBC.…”
Section: Discussionmentioning
confidence: 72%
“…Mounting evidence suggests that flotillins may not be merely passive raft scaffolders, but active signaling molecules involved in several cellular processes . Flotillins have recently been implicated in the tumorigenesis of several cancers such as breast cancer, gastric cancer and renal cell carcinoma . This study revealed an important function of flotillin‐1 in H‐Ras activation and invasion in breast cancer cells.…”
Section: Discussionmentioning
confidence: 74%
“…FLOT2 was reported to be deregulated and associated with progression and poor survival in numerous types of cancer [24,25], making it a critical regulator of tumour initiation and prognosis. For example, the upregulation of FLOT2 was observed in renal cell carcinoma, and was association with poorer prognosis and overall survival of patients [26]. High expression of FLOT2 was also reported in cervical carcinoma and is associated with poor clinical survival of patients with cervical carcinoma [27].…”
Section: Discussionmentioning
confidence: 99%
“…Flot2, a highly conserved 47-kDa protein located in a region on human chromosome 17q11.2, is originally characterized as an obbligato part of lipid raft domains that tether growth factor receptors linked to signal transduction pathways [30,31]. Recently, emerging evidence has demonstrated that Flot2 , a downstream gene of p53 family members [32], might be involved in the progression of metastasis in several kinds of solid tumors, including gastric carcinoma [33], breast cancer [34], renal cell carcinoma [35] and lung adenocarcinoma [36]. Zhao et al [37] recently suggested that in nasopharyngeal carcinoma, Flot2 is an indispensable member for transforming growth factor-β (TGF-β) family signaling, which epithelial cells receive from their micro-environment to drive EMT during cancer progression [3840].…”
Section: Discussionmentioning
confidence: 99%